Spatio-temporal visualization of soil dissolved organic carbon production and mobilization in a high-elevation Andean catchment - Pesántez, Juan Pablo (2024)
The visualization of dissolved organic carbon (DOC) spatial patterns can be a valuable tool for a comprehensive understanding of DOC production and transport processes within a catchment (Birkel et al., 2017; Pesántez, Birkel, Mosquera, et al., 2023; Wu et al., 2014). Visualizations of catchment fluxes, storages, and water ages, for instance, have already provided a key technique for enhancing our understanding of hydrological catchment functioning in various eco systems (Smith et al., 2022; Van Huijgevoort et al., 2016b). The Spa tially Distributed Tracer-Aided Rainfall-Runoff Model (STARR) offers the opportunity to represent hydrological processes, but also to incor porate tracers for validating hydrological processes (van Huijgevoort et al., 2016a), as highlighted below.